2012
DOI: 10.1097/bcr.0b013e3182335a14
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Older Adults in Burn Prevention Education

Abstract: The objective of the study is to educate New York City seniors aged 60 years and older about fire safety and burn prevention through the use of a community-based, culturally sensitive delivery platform. The ultimate goal is to reduce burn injury morbidity and mortality among this at-risk population. Programming was developed and provided to older adults attending community-based senior centers. Topics included etiology of injury, factors contributing to burn injuries, methods of prevention, emergency preparedn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…They found the majority of the programs focused on smoke alarm interventions [14,15] and improving children's fire safety knowledge [16,17]. HFS information has not been widely disseminated among older adults [18]. Though few studies were found directed toward older adults [10,18], none have combined an education intervention with a HFS assessment and measured retention of fire prevention knowledge over time.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…They found the majority of the programs focused on smoke alarm interventions [14,15] and improving children's fire safety knowledge [16,17]. HFS information has not been widely disseminated among older adults [18]. Though few studies were found directed toward older adults [10,18], none have combined an education intervention with a HFS assessment and measured retention of fire prevention knowledge over time.…”
Section: Discussionmentioning
confidence: 96%
“…HFS information has not been widely disseminated among older adults [18]. Though few studies were found directed toward older adults [10,18], none have combined an education intervention with a HFS assessment and measured retention of fire prevention knowledge over time. This study is a first step toward addressing this gap in the literature.…”
Section: Discussionmentioning
confidence: 98%